Using General Collective Intelligence to Re-think Decision-Systems and Other Information Technologies & Information Systems to Better Inform Pandemic Responses - Williams, Andy (My University, 2022)
The emerging science of Human-Centric Functional Modeling uses functional state spaces to provide a completely self-contained representation of human perceptions in the functional domain of each consciously observable human system (body, emotions, mind, consciousness). In the case of the cognitive system (mind) this constitutes a complete semantic model of information. This semantic model is required to implement a General Collective Intelligence software platform hypothesized to be capable of acting as a collective cognition that significantly increases capacity for group problem-solving through collective reasoning. This paper explores how the lack of this General Collective Intelligence based decision-making platform, and hence the lack of this semantic modeling, might be a systemic error in all group decisions, including policy decisions, with the result of preventing governments from achieving optimal outcomes with regards to the COVID-19 pandemic. This paper also explores why this newly emerging science of General Collective Intelligence or GCI as a model of collective decision-making is predicted to radically increase capacity to solve collective problems, and why this is predicted to radically impact COVID-19 response policy.
Keywords: COVID; functional state space; General Collective Intelligence; Human-Centric Functional Modeling; system dynamics